U-Pb geochronology of the Lime Hill gneissic complex, Cape Breton Island, Nova Scotia - Sangster, A.; Hunt, P.; Mortensen, J. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1990)
Low-grade metasedimentary rocks of Late Proterozoic age in the Bras d'Or Terrane of Cape Breton Island contain small areas of gneissic rocks which were previously undated. New U-Pb data indicate that the Lime Hill gneissic complex is the product of an Early Cambrian intrusive/metamorphic event Two intrusions at Lime Hill give similar ages which indicate that emplacement and deformation of foliated tonalitic orthogneiss were followed very quickly by intrusion of massive granitic dykes at about 540 to S4S Ma. U-Pb analyses of metamorphic monazite from the Lime Hill paragneiss indicate that these rocks last cooled through the closure temperature of the U-Pb system for monazite (650-700°C) at about 549 Ma. All zircon fractions analyzed from the tonalitic orthogneiss and granitic dyke contain older inherited zircons which yield an apparent age range of at least 1.4 to 23 Ga. The presence of an inherited monazite component may suggest that the rocks have been affected by an older metamorphic event and are in fact older than the Malagawatch Formation, as suggested by published ore lead isotopic values.